The Effectiveness of the Problem-Based Learning Model to Improve the Students’ 21st Century Skills - Yanto, Febri; Enjoni, Enjoni (Indonesian Research Journal in Education |IRJE|, 2022)
The 21st century learning must develop the students’ 21st century competencies, including aspects of knowledge, students’ problem solving skills, and science process skills. These student skills need to be widely developed in science learning to face the challenges of the century. This study aimed to determine the effect of PBL on students’ 21st century skills. The study method was quasi-experimental, using a posttest only randomized control group design. Data analysis used a comparison test of two sample groups and the Mann-Whitney U test. The analysis results of student science process activities were 84% in the very active category, while problem solving skills were 0.001 < 0.05 and 0.000 < 0.05 at SMA N 8 and SMA N 9 Padang. Meanwhile, the analysis results of the knowledge aspect data obtained 0.000 <0.05 and 0.000 <0.05 at SMA N 8 and SMA N 9 Padang with the conclusion that Ho was rejected, and it means that in the problem solving aspect and the knowledge aspect there was an influence of PBL on student 21st century skills in the aspects of knowledge, skills problem solving, and students’ science process skills.